Experimental study of polymeric stent fabrication using homemade 3D printing system. Issue 6 (21st March 2019) - Zhao, Danyang; Zhou, Ruiqi; Sun, Jianxing; Li, Hongxia; Jin, Yifei
Abstract : Biodegradable polymeric stents have received extensive attention due to the high efficiency in interventional therapy. Fabrication of well‐defined polymeric stents still poses a significant fabrication challenge. This study aims to investigate the feasibility of using a homemade three‐dimensional (3D) printing system to directly print customized polymeric stents. In the proposed system, a rotating shaft with controllable temperature and rotating speed has been integrated into a fused deposition modeling‐based 3D printing system to support the printed stents stably in situ . In addition, the effects of operating conditions including the rotating speed, printing temperature, printing speed, and step distance on the dimensions of the 3D printed stents have been investigated. Furthermore, orthogonal experiments have been designed and performed to comprehensively explore the significance of each processing parameter. Finally, based on the obtained knowledge, polymeric stents with various structures have been successfully 3D printed using the homemade 3D printing system with relatively high shape fidelity. POLYM. ENG. SCI., 59:1122–1131 2019. © 2019 Society of Plastics Engineers